Mussel Shell Powder as Bio-adsorbent of Heavy Metals in Water - Darjati, Darjati; Marlik, Marlik (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
—